FACTORS RELATED TO THE INTENTION ON VOLUNTARY BLOOD DONATION IN BLOOD DONOR SERVICE (UDD) INDONESIAN RED CROSS (PMI) YOGYAKARTA - Windadari Murni Hartini; Fatwa Sari Tetra Dewi; Sulanto Saleh Danu; Theodola Baning Rahayujati (Pusat Riset dan Inovasi Nasional, 2021)
Background: Blood transfusion is a valuable aid to handle patients with severe anemia, inherited blood disorders, severe injury, surgery, liver disease, and reduce maternal mortality. In Indonesia, about 500,000 pregnant women die each year, 28% of them due to loss of blood. Theory of planned behavior Ajzen is used to study the intention to donate blood on a regular voluntary blood donors. Objective: to know the relationship between attitude, subjective norm and PBC with intention to donate blood regularly in blood donor service (udd) Indonesian Red Cross (pmi) Yogyakarta Method: This is an observational Study with cross sectional design. The Sample uses a systematic random sampling method with 276 respondents. The Measuring instruments are a questionnaire to take explanatory test and test-try questionnaire. Analysis of data used a product moment correlation and multiple linear regression.Results: Respondents had positive attitude, subjective norm and PBC to the intention. Significant relationship with intention on attitude variables (r-value = 0.330, p = 0.000), subjective norm (r-value = 0.341, p = 0.000), and PBC (r-value = 0.362, p = 0.000). The role of each variable based on regression coefficients obtained by the equation to donate blood regularly = 7.682 + 0.175 attitude + 0.215 subjective norms + 0.191 PBC. Adjusted R Square value of 0.20 indicates a 20% change of intention is influenced by attitude, subjective norm and PBC.Conclusion: There is a significant relationship between attitude, subjective norm and PBC with intention to donate blood regularly. Subjective norm has the largest positive effect (0.215) to the intention compared with PBC (0191) and attitudes (0175).